Rethinking Public Relations - Moloney, Kevin (Routledge, 2006)
All PR, whether for charities or arms manufacturers, is weak propaganda. Though it has its undeniable benefits (it grabs attention and helps circulate more information), it also has costs (such as selective messaging). This extensively revised edition of a classic text fully investigates PR, updating and expanding earlier arguments and building upon the successful first edition with new thoughts, data and evidence.